THE STRATEGIC POSITION OF BRIN'S BUSINESS INCUBATOR SERVICE AS A CATALYST FOR NATIONAL RESEARCH AND INNOVATION DOWNSTREAMING: AN INTEGRATED MCKINSEY 7S, PESTEL, AND SWOT ANALYSIS - Arif Ardiawan; Siti Jahroh; Suhendi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This article analyzes the strategic position of the Business Incubation Service (LIB) at the National Research and Innovation Agency (BRIN) as a catalyst for the downstreaming of national research and innovation by integrating McKinsey 7S, PESTEL, and SWOT frameworks. This descriptive qualitative study uses primary data from observations and in-depth interviews with LIB BRIN managers, tenants, other incubator managers, and venture capitalists, as well as secondary data from official documents and policies related to research downstreaming. The PESTEL analysis reveals opportunities against the backdrop of threats from regulatory dynamics, fiscal pressures, and low national technological readiness, such as BRIN’s potential as an orchestrator of national technology incubators, a large and diverse domestic market, green economy trends, and ease of global networking. Through McKinsey 7S, LIB BRIN is identified as having strategic strengths such as relatively stable funding from research endowment funds, broad access to research resources, a focus on research-based incubation, and a strong identity as a research-based incubator. However, it still faces weaknesses, including the lack of dedicated incubation buildings, gaps in business mentor human capital competencies, limited ease of research access for entrepreneurs, and an immature service system. Integrating the 7S and PESTEL findings into a SWOT analysis shows that LIB BRIN’s strengths and opportunities outweigh its weaknesses and threats, indicating that the institution possesses strategic capital to strengthen its role in research downstreaming, with implications for the need to enhance governance, improve human capital capacity, develop supporting infrastructure, and mature a network-based incubation model with cross‑institutional collaboration.